Rapid synthesis: Innovative models for the delivery of pharmacy services in rural and remote areas - Waddell, K; Ali, A; Bain, T; Bhuiya, AR; Dass, R; Grewal, E; DeMaio, P; Wilson, MG (My University, 2023)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about innovative models for the delivery of pharmacy services in rural and remote areas in response to a decision-maker's request.
Keywords: models; delivery; pharmacy; services; rural; remote